Discourse processing: an interview with Professor Evelyn Ferstl - Ferstl, Evelyn C.; Limberger, Bernardo Kolling; Buchweitz, Augusto (Letrônica, 2018)
— *** Processamento do discurso: uma entrevista com Evelyn Ferstl *** —